Bentuk Verbal “Ngaba” Dalam Bahasa Bali: Kajian Metabahasa - Ryandika, I Wayan Wira; Mastini, Gusti Nyoman; Sentana, Gek Diah Desi (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
This research aims to determine the verbal “ngaba” in Sebatu village. The data source in this research is a collection of data obtained from interviews with several communities as sources regarding the verbal “ngaba” in Sebatu village. The method of collecting data in this research is through interview, observation, and literature study. Natural Semantic Metalanguage used to analyze verbal “ngaba” in Sebatu village. Verbal “ngaba” in Balinase Language especially Sebatu village has 41 equivalent form as follows: “nyuun, nengklek, mundut, nangal, ngemu, nyanggem, negen, nengelong, ngundit, nikul, ngéndot, nyunggi, nengkalung, ngandong, nyelepit, nyangkol, nyingal, nyangkil, nyelet, nyungkelit, ngadut, mungsel, ngondos, ngabin, nempong, ngembel, nyekel, ngepit, ngéncét, nampa, ngrampa, manjer, ngee, nyepit, dongdéng, ningting, ngoros, néngténg, natad, nandan, and nyabit.” The equivalent of verbal “ngaba” in Balinase language especially Sebatu village dialect has their own differences that can be seen from the way that word is used that related to the tools, places, subject, and object when the word “bring” is used.